Epidural analgesia with sufentanil in relation to OPRM1 and ABCB1 polymorphisms - Bartošová, Olga; Polanecký, Ondřej; Šachl, Robert; Netíková Štenglová, Irena; Perlík, František; Adámek, Svatopluk; Lischke, Robert; Slanař, Ondřej (Physiological research, 2019)
The aim of this study was to evaluate the association between OPRM1 and ABCB1 polymorphisms on pain relief with epidural sufentanil in 69 patients after rectosigma resection for cancer. The median number of injections (SD) 2.31 (1.36), IQR=1, required by 118AA subjects was significantly lower in comparison with 118AG group 5.25 (3.13), IQR=6.5, (chi(2)=9.75, p=0.001); correspondingly median drug consumption of 1.16 (0.79), IQR=1.083, defined daily doses (DDD) was significantly less in the 118AA group in comparison with 2.14 (1.17), IQR=2.23, DDD in 118AG subjects, (chi(2)=7.00, p=0.008). Opioid-induced adverse effects were observed in 15 % and 33 % of patients in 118AA and 118AG groups, respectively (chi(2)=8.16, p=0.004). The median number of injections (SD) required by women and men was 3.30 (2.16), IQR=2, and 2.80 (1.59), IQR=1, respectively (chi(2)=6.25, p=0.012). Opioid-induced adverse effects were observed in 26 % and 12 % of women and men, respectively (chi(2)=5.49, p=0.011). Heterozygotes of OPRM1 polymorphism and women were more difficult to treat subpopulations that required higher doses of rescue analgesic medication and suffered more adverse effects.
Keywords: Prospective Studies; senioři nad 80 let; Sufentanil; Humans; Pain Management; lidé středního věku; sufentanil; prospektivní studie; Aged, 80 and over; Middle Aged; epidurální analgezie; Polymorphism, Genetic; P-glykoproteiny; mužské pohlaví; polymorfismus genetický; Analgesia, Epidural; Pain, Postoperative; Receptors, Opioid, mu; receptory opiátové mu; pooperační bolest; ATP Binding Cassette Transporter, Subfamily B; ženské pohlaví; Analgesics, Opioid; kolorektální nádory; lidé; management bolesti; Aged; senioři; Male; opioidní analgetika; Colorectal Neoplasms; Female